Readmission and Resource Utilization in Patients From Socioeconomically Distressed Communities Following Lumbar Fusion. Issue 4 (21st May 2023) - Siegel, Nicholas; Lambrechts, Mark J.; Karamian, Brian A.; Carter, Michael; Magnuson, Justin A.; Toci, Gregory R.; Krueger, Chad A.; Canseco, Jose A.; Woods, Barrett I.; Kaye, David; Hilibrand, Alan S.; Kepler, Christopher K.; et al.
Abstract : Study Design: Retrospective cohort study. Objective: To determine whether: (1) patients from communities of socioeconomic distress have higher readmission rates or postoperative healthcare resource utilization and (2) there are differences in patient-reported outcome measures (PROMs) based on socioeconomic distress. Summary of Background Data: Socioeconomic disparities affect health outcomes, but little evidence exists demonstrating the impact of socioeconomic distress on postoperative resource utilization or PROMs. Methods: A retrospective review was performed on patients who underwent lumbar fusion at a single tertiary academic center from January 1, 2011 to June 30, 2021. Patients were classified according to the distressed communities index. Hospital readmission, postoperative prescriptions, patient telephone calls, follow-up office visits, and PROMs were recorded. Multivariate analysis with logistic, negative binomial regression or Poisson regression were used to investigate the effects of distressed communities index on postoperative resource utilization. Alpha was set at P <0.05. Results: A total of 4472 patients were included for analysis. Readmission risk was higher in distressed communities (odds ratio, 1.75; 95% confidence interval, 1.06–2.87; P =0.028). Patients from distressed communities (odds ratio, 3.94; 95% confidence interval, 1.60–9.72; P =0.003) were also more likely to be readmitted for medical, but not surgical causes ( P =0.514), and distressed patients had worse preoperative (visual analog-scale Back, P <0.001) and postoperative (Oswestry disability index, P =0.048; visual analog-scale Leg, P =0.013) PROMs, while maintaining similar magnitudes of clinical improvement. Patients from distressed communities were more likely to be discharged to a nursing facility and inpatient rehabilitation unit (25.5%, P =0.032). The race was not independently associated with readmissions ( P =0.228). Conclusion: Socioeconomic distress is associated with increased postoperative health resource utilization. Patients from distressed communities have worse preoperative PROMs, but the overall magnitude of improvement is similar across all classes. Level of Evidence: Level IV.